Shifting the Superparamagnetic Limit of Nanosized Copper Iron Spinel - Stewart, Silvana Jacqueline (2003)
Using a co-precipitation method, a system formed by nanocrystalline Cu-Fe spinel, grain size D = 6 nm, and CuO (15 wt.%) was obtained. A Mossbauer blocking temperature (T B ) of the spinel particles that lies between 100 and 200 K was observed. T B progressively increases as the sample is subjected to high-energy ball milling, being higher than 298 K after milling for 10 hours. The magnetic results also showed the increment of T B . The maxima of the in-phase component of the AC susceptibility at T max shift toward higher temperatures with the milling After 4 hours, this shift is ≈70 K for all the AC field frequencies. Simultaneously, the increase in the mean grain sizes (up to D = 13 nm) and the decrease of the microstrain level indicate that the degree of crystallinity of the spinel phase increases with the milling. After milling for 10 h, the sample is only composed by copper iron spinel with cubic structure.